SMCε, a coastal modeling system for assessing beach processes and coastal interventions: Application to the Brazilian coast. (June 2019) - Quetzalcóatl, O.; González, M.; Cánovas, V.; Medina, R.; Espejo, A.; Klein, A.; Tessler, M.G.; Almeida, L.R.; Jaramillo, C.; Garnier, R.; Kakeh, N.; González-Ondina, J.
Abstract: A user-friendly system designed to understand local littoral processes and design/evaluate coastal interventions, named the Coastal Modeling System (SMC ε ) is presented. The system, which comprises a set of numerical models, state-of-the-art methodologies and numerical databases, is prepared to provide a method for coastal practitioners, researchers and decision-makers to address coastal issues, such as erosion and flooding or to evaluate coastal defense structures. The system incorporates a method to transfer numerically generated, calibrated and validated wave series to the surf zone; to estimate the sediment littoral drift by means of up-to-date formulations; and to estimate the flooding level and impacts such as those produced by climate change. In this paper, these skills are detailed. The system, which is adaptable to any coastal region, was implemented for the Brazilian coast (SMC-Brasil). The implementation includes databases and methodological adaptations to local characteristics, a dissemination plan and the development of several study cases. Highlights: SMCε is modeling software to deal with all stages of Coastal Engineering Projects. Database includes 60-year time series of waves, storm surge and astronomical tide. Methodology/models to study dynamics/impacts at all scales including climate change. Erosion/flooding assessment due to interventions/natural causes even climate change. SMCε is free and adaptable to any country. Adaption to Brazilian coast is described.